2010
DOI: 10.1177/0333102410392068
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal neuroimaging in a child with sporadic hemiplegic migraine: A contribution to understanding pathogenesis

Abstract: Multimodal neuroimaging (MRI, DWI, MRS, SPET) in a prolonged HM attack supports evidence for a primary neuronal dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 13 publications
2
42
0
1
Order By: Relevance
“…The hypothesis of a mitochondrial deficiency was also put forward by a study in which decreased NAA was found in the (left) thalamus of MwoA patients (36). Finally, a reduced NAA concentration was also found at rest in the cerebellum of FHM1 patients (37), in the left temporoparietal cortex (site of migrainous stroke) of a sporadic hemiplegic migraine (SHM) patient (38) and in the occipital cortex of another SHM patient (39), which has been rather attributed to neuronal impairment or loss. The latter is obvious in migrainous stroke but may also fit with the frequently observed cerebellar atrophy in FHM (40).…”
Section: Naamentioning
confidence: 91%
See 4 more Smart Citations
“…The hypothesis of a mitochondrial deficiency was also put forward by a study in which decreased NAA was found in the (left) thalamus of MwoA patients (36). Finally, a reduced NAA concentration was also found at rest in the cerebellum of FHM1 patients (37), in the left temporoparietal cortex (site of migrainous stroke) of a sporadic hemiplegic migraine (SHM) patient (38) and in the occipital cortex of another SHM patient (39), which has been rather attributed to neuronal impairment or loss. The latter is obvious in migrainous stroke but may also fit with the frequently observed cerebellar atrophy in FHM (40).…”
Section: Naamentioning
confidence: 91%
“…All but five studies (9,18,19,37,39) reported the age-ranges of both migraine patients and controls.…”
Section: Age and Gendermentioning
confidence: 99%
See 3 more Smart Citations